2009
DOI: 10.1080/08860220902780119
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Renal Function Impairment to Unexplained Troponin T Elevations in Congestive Heart Failure

Abstract: Background. Patients with severe congestive heart failure (CHF) often have unexplained elevations in serum concentrations of troponin T (TnT), and it is proposed that this is due to cardiac TnT release because of underlying cardiac disease. We investigated whether impaired renal function is an additional underlying phenomenon contributing to increased TnT levels in patients with CHF. Methods. Sixty-two patients with nonischemic CHF, New York Heart Association (NYHA) class III-IV, with normal coronary angiogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Non-inclusion criteria were refusal of consent, presentation >5 days after symptom onset, recent anticoagulant treatment, severe renal dysfunction and cancer therapy. Rationales for the exclusion criteria were the normalisation of the cTnT level five days after ACS, the fact that cTnT may be increased even in the absence of clinically suspected acute myocardial ischemia in patients with renal insufficiency, and the unpredictable effect of anticoagulant treatment and cancer therapy on the biomarkers' concentration [12,13]. …”
Section: Methodsmentioning
confidence: 99%
“…Non-inclusion criteria were refusal of consent, presentation >5 days after symptom onset, recent anticoagulant treatment, severe renal dysfunction and cancer therapy. Rationales for the exclusion criteria were the normalisation of the cTnT level five days after ACS, the fact that cTnT may be increased even in the absence of clinically suspected acute myocardial ischemia in patients with renal insufficiency, and the unpredictable effect of anticoagulant treatment and cancer therapy on the biomarkers' concentration [12,13]. …”
Section: Methodsmentioning
confidence: 99%
“…17 Furthermore, new studies should be carried out to determine whether previously observed non-CVD specific elevation of circulating cTnT in patients with chronic kidney disease or reduced GFR is maintained with the application of new high sensitivity assays in comparison to cTnI, which previously demonstrated better correlation to true myocardial injury in the same patient cohorts. [18][19][20] In terms of sex differences in cardiac arrest, several studies have shown that women who suffer a cardiac arrest have higher survival to hospital admission but worse prognosis in the hospital. [21][22][23] It is speculated that the reason women may have increased survival to the hospital is that women are more likely to activate vagal compensatory mechanisms in response to abrupt coronary occlusion, which have beneficial antiarrythmic effects.…”
mentioning
confidence: 99%
“…And the authors postulated that it is the impaired renal function that causes the accumulation of troponin. 16,17 Factors associated with elevated TAKI such as previous heart disease and advanced age suggest that these patients were more likely to have underlying heart disease and therefore possibly higher basal serum troponin concentrations. A study investigating the plasma elimination of cardiac troponin I after acute myocardial infarction in ESRD showed increased half-life in those patients with ESRD compared with normal patients.…”
Section: Discussionmentioning
confidence: 99%